2015
DOI: 10.1039/c4em00472h
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects and bioaccumulation of pharmaceutically active compounds in crucian carp caged near the outfall of a sewage treatment plant

Abstract: Pharmaceutically active compounds (PhACs) have been universally detected in rivers, lakes and coastal waters that are affected by effluents from sewage treatment plants (STPs). In this study, the biological effects and bioaccumulation of PhACs were assessed in crucian carp (Carassius auratus) caged in an effluent-receiving river for 21 days. Compared with control fish in the laboratory and at a reference site, a significant reduction in hepatosomatic index (HSI) and increase in the biotransformation enzymes et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Representative results are shown as star plot charts indicating the deviation of all biomarkers in relation to the control (0) (Sanchez et al, 2013). In addition, data were analyzed using a weighing procedure for endpoints as previously described (Liu et al, 2013(Liu et al, , 2015, assuming that a biochemical alteration has lower impact on the organism health than changes at an individual level. Behavior is considered as the outcome of many biological processes resultant from interactions between the organisms and the surrounding environment (Oliveira et al, 2015).…”
Section: Integrated Biomarker Response (Ibr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Representative results are shown as star plot charts indicating the deviation of all biomarkers in relation to the control (0) (Sanchez et al, 2013). In addition, data were analyzed using a weighing procedure for endpoints as previously described (Liu et al, 2013(Liu et al, , 2015, assuming that a biochemical alteration has lower impact on the organism health than changes at an individual level. Behavior is considered as the outcome of many biological processes resultant from interactions between the organisms and the surrounding environment (Oliveira et al, 2015).…”
Section: Integrated Biomarker Response (Ibr)mentioning
confidence: 99%
“…6B1-B5), it seems clear that GEM had more effects in terms of capability to swim against a flow of S. aurata, CAT and GR activities in gills and GPx and GR activities in liver. If the data analyses takes into account a weighing factor attributed to different biological levels of organization as suggested by Liu et al (2013Liu et al ( , 2015, the effects of the different concentrations of GEM would be ordered as follows: 150 μgL −1 ≈ 15,000 μg.L −1 ≈ 1500 μgL −1 > 1.5 μgL −1 ≈ 15 μgL −1 (Table S2). This data analysis, attributing a higher weighing factor to behavior, did, however, not alter the ranking of GEM impact.…”
Section: Biological Responsesmentioning
confidence: 99%
“…Therefore, a growing interest has been given to the risk of pharmaceuticals posing for the aquatic trophic chains (Brodin et al, 2014;Chèvre, 2014;Zenker et al, 2014). In a field study investigating the bioaccumulation of various pharmaceuticals in the liver of crucian carp (Carassius auratus) caged in an effluent-receiving river, PRP has showed a higher bioaccumulation factor (BAF) (2782) than the other pharmaceutical substances such as roxithromycin (440), carbamazepine (917) and erythromycin (1482) (Liu et al, 2015a). Moreover, PRP is considered lipophilic (logK ow = 2.43-3.65), highly resistant to hydrolysis (half-life of N 1 year), bioavailable and mobile in the environment, suggesting its bioaccumulation potential in the water ecosystems (Bendz et al, 2005;Massarsky et al, 2011;Maszkowska et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Although designed for human use, more and more evidence has indicated that propranolol may pose harm to aquatic organisms [10][11][12][13][14][15], it must be pointed out that propranolol has shown high hydrolytic stability [16]. Meanwhile, propranolol may bioaccumulate in water ecosystems due to its lipophilicity [2,3,17]. Therefore, it is urgent that various efficient methods are developed to remove propranolol from water.…”
Section: Introductionmentioning
confidence: 99%